The Interplay of Magnetism and Thermoelectricity: A Review - Liu, Shuo; Chen, Mengzhao; Fu, Chenguang; Zhu, Tiejun (Advanced Physics Research, 2023)
The introduction of magnetism into a solid material might significantly modulate its electronic transport behavior, thereby serving as a means to tune the thermoelectric properties that have attracted considerable research attention in recent years. In this review, an introduction to recent studies on the interplay of magnetism and the thermoelectric Seebeck and Nernst effects is given. Concerning the Seebeck effect, the influence of superparamagnetic nanoparticles on the electronic and phonon transport of conventional nonmagnetic thermoelectric materials, as well as the spin‐related thermoelectric transport phenomenon in magnetic materials, are discussed. Then, the Nernst effect‐related transverse thermoelectric transport properties in nonmagnetic and magnetic topological materials are summarized, followed by a short introduction to the Nernst devices. Last, a further outlook on this new research direction is offered.